2017
DOI: 10.1002/ana.25069
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of phenotypic severity in mucopolysaccharidosis type IIIA

Abstract: ObjectiveMucopolysaccharidosis IIIA or Sanfilippo disease type A is a progressive neurodegenerative disorder presenting in early childhood, caused by an inherited deficiency of the lysosomal hydrolase sulfamidase. New missense mutations, for which genotype–phenotype correlations are currently unknown, are frequently reported, hampering early prediction of phenotypic severity and efficacy assessment of new disease‐modifying treatments. We aimed to design a method to determine phenotypic severity early in the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…Enzyme activity levels in patient's cells generally cannot predict phenotype severity or progression [174,[190][191][192]. However, a recent study was able to differentiate slow progressing cases of MPS IIIA by an increase of sulfaminidase activity in patient's skin fibroblasts cultured at lower temperature (30 • C) [193].…”
Section: Biomarkers Of Mps III Suitable For Diagnosis Clinical Evalumentioning
confidence: 99%
“…Enzyme activity levels in patient's cells generally cannot predict phenotype severity or progression [174,[190][191][192]. However, a recent study was able to differentiate slow progressing cases of MPS IIIA by an increase of sulfaminidase activity in patient's skin fibroblasts cultured at lower temperature (30 • C) [193].…”
Section: Biomarkers Of Mps III Suitable For Diagnosis Clinical Evalumentioning
confidence: 99%
“…Molecular characterization of LSDs has shown that in most of the cases the disease is caused by missense mutations [37,38]. Pathophysiological studies in different LSDs have suggested that in some cases, the amino acid change leads to loss of protein stability due to changes in their processing, folding, glycosylation, and pH stability, which promotes aggregation and can induce ER or Golgi apparatus retention and/or increased degradation, or defective transport to the lysosomes [37][38][39][40][41][42][43][44][45][46][47][48]. In this sense, the use of PCs as an alternative to restore the folding and trafficking of the mutated lysosomal proteins has been proposed [19,20].…”
Section: Use Of Pharmacological Chaperones In Lsdsmentioning
confidence: 99%
“…Based on a systematic data collection, currently more than 100 disease‐causing ASS1 genetic variants are known; however, the impact of the genotype on the phenotypic presentation remains insufficiently understood . Given that residual enzymatic activities have already been reported to predict disease severity and survival rates in other inborn errors of metabolism, such as Farber disease and mucopolysaccharidosis type IIIA and VII, we hypothesized that ASS1 enzyme activity may correlate with disease severity in CTLN1.…”
Section: Introductionmentioning
confidence: 97%